#### Answer

$m^{2}+1.4m+0.49$

#### Work Step by Step

Expand $(m+0.7)^{2}$:
$(m+0.7)^{2}=m^{2}+2m(0.7)+(0.7)^{2}=m^{2}+1.4m+0.49$.

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$m^{2}+1.4m+0.49$

Expand $(m+0.7)^{2}$:
$(m+0.7)^{2}=m^{2}+2m(0.7)+(0.7)^{2}=m^{2}+1.4m+0.49$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.